2015
DOI: 10.1002/2015ja021320
|View full text |Cite
|
Sign up to set email alerts
|

Study of equatorial E region irregularities using rare daytime VHF scintillation observations

Abstract: Scintillations on VHF radio signal are sparsely observed during daytime due to unavailability of strong electron density irregularities in equatorial E or F region. Type I/II irregularities observed at E region altitudes during the daytime are linked with either two‐stream or gradient drift instability. The occurrence of these irregularities in presence of strong blanketing Es (Esb) can produce weak‐moderate scintillations on VHF signal during daytime. Such sparse daytime VHF scintillations are used in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Similarly, using spaced receiver VHF scintillation measurements, recently, Yadav et al . [] have shown that zonal drifts are having drift speeds on the order of 120 m/s. On the other hand, the temporal variations of zonal drifts also suggest higher eastward drifts during evening hours at PRE times, while they show slow reduction of these drifts to westward in the late nights.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, using spaced receiver VHF scintillation measurements, recently, Yadav et al . [] have shown that zonal drifts are having drift speeds on the order of 120 m/s. On the other hand, the temporal variations of zonal drifts also suggest higher eastward drifts during evening hours at PRE times, while they show slow reduction of these drifts to westward in the late nights.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is applicable to both weak and strong scintillations unlike power spectral analysis technique, which is valid for only weak scintillations. Recently, Yadav et al [] examined the spatial structures of E region long‐wavelength irregularities using daytime spaced receiver VHF scintillation observations. Besides this it can be used to get the zonal irregularity drift.…”
Section: Introductionmentioning
confidence: 99%
“…Arras () estimated global Es occurrence using GPS radio occultation technique, which indicates that Es occurrence is maximum at mid latitudes in local summer. On rare occasions E region irregularities, in presence of Esb, can produce scintillations of radio signals in VHF band (Yadav et al, ). The main difference is that, unlike Esb layer, the ionization in nonblanketing Es layers is not high enough to blanket the upper ionospheric layers to the radio signal transmitted from ground‐based ionosonde.…”
Section: Introductionmentioning
confidence: 99%